The Effect of Trust In The Soco Community on Repurchase Intention in Social E-Commerce - Roseline, Klaudia; Gunadi, Willy (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The virtual community strategy is a marketing strategy that is interactive, inexpensive, influential, and can increase sales for e-commerce. Sociolla is the largest beauty e-commerce that has a SOCO virtual community platform. With advanced technology, SOCO's community platform has many features to encourage product and beauty-related reviews, discussions, and topics. The purpose of this study is to analyze the relationship between familiarity, perceived similarity, social network, structural assurance, trust propensity, impression management, Trust in members, trust in the website, intention to get information, and repurchase intention among members of the Sociolla virtual community, who is domiciled in Jakarta. Using PLS-SEM analysis, Bogor, Depok, Tangerang, and Bekasi have purchased on the Sociolla site in the last six months. Rust is essential because beauty products depend on each user's skin condition. This research concludes that structural assurance, trust propensity, and impression management significantly affect Trust in members. Trust propensity and impression management significantly ultimately affect the Trust in the website. Confidence in members and Trust in the website significantly positively affect the intention to get information. Trust in members and Trust in the website significantly positively affect the repurchase intention.